Empowerment Through Mystical Experiences in Islam: A Literature Study on Muhammad PBUH’s First Revelation of Islam. - Dini Rahma Bintari (Unisia, 2015)
This paper discusses how empowerment can be triggered by mystical experiences, byfocusing on mystical experience of the first revelation of Islam to Muhammad PBUH. Only fewliterature on empowerment in mainstream psychology, specifically discuss how empowermentcan be achieved through personal mystical or spiritual experiences. Transpersonal studies giveexplanations of human mystical experiences and extra sensory perceptions. Chronologicalanalysis of the first revelation showed how the mystical experience empowered Muhammad.First, mystical experience is empowerment. Second, mystical experiences can become aneffective and an efficient trigger for empowerment in daily life if understood correctly; andaffirmed with social support. Third, spiritual awakening can unfold into intrapersonal,interpersonal and behavioral empowerment if the person contemplates about the experience,and implement it to benefit others.